EXAMINATION OF THE EFFICACY OF A CHRONIC DISEASE SELF-MANAGEMENTRAMME (CDSMP) FOR PATIENTS WITH INFLAMMATORY BOWEL DISEASE (IBD): A PILOT STUDY. (8th June 2013) - Forry, M; McDonnell, E; Wilson O'Raghallaigh, J; Kelly, O; O'Toole, A; Patchett, S
Abstract : Introduction: The need for a psychosocial intervention for patients with IBD was recognised by multidisciplinary healthcare professionals working at a large Irish teaching hospital. CDSMP, developed by Stanford University, was identified as a leading model of psychosocial intervention. Run over 6 weeks in 2.5 hour weekly sessions and delivered by two people, one of whom must have a chronic illness, the CDSMP focuses on action planning and goal setting, using brainstorming exercises to help develop self management techniques. Aims/Background: To pilot the use of a CDSMP in patients with IBD. Method: A repeated measures design with wait list control (n=44) was utilised. Mood and general health related quality of life (HRQoL) were assessed using the Hospital Anxiety and Depression scale (HADS) and Rand 36-Item Health Survey (SF-36). The Short Inflammatory Bowel Disease Questionnaire (SIBDQ) was used to measure physical, social, and emotional status in patients with IBD. Qualitative descriptions of problems caused by chronic disease were noted the beginning and end of the six week intervention. Results: 44 patients participated in the pilot study, 11 male (25%) and 33 female (75%). Significant improvement in mood was achieved in treatment group with paired sample t-tests indicated significant reduction in levels of depression on the HADS (p=0.05). At baseline, 14% of the treatment group displayed mild depression. Post-intervention no clinical levels of depression were evident in the treatment group compared to 17% of waitlist control who displayed mild to severe levels of depression. Significant improvement was noted in the SF-36 on the factor of emotional well-being (p=0.04). There was also an improvement in the qualitative descriptions of problems related to chronic disease. Of note, 14% of the treatment group were experiencing relapses in their condition at the end of the CDSMP. Conclusion: The results of this study indicate that CDSMP appears to be an effective psychosocial intervention for patients with IBD. Implementation of a CDSMP in hospital and community settings in Ireland for this patient group should be considered.